(untitled) (Socio-economic relations in the digital society, 2019)
The article describes financial aspects of using budget resources and functioning of nature management and nature protection activities to solve the main problems of environmental protection of the country. The implementation of the Kyoto Protocol by Ukraine is analyzed. It aimstostabilize the concentration of green house gases that cause global warming, in the atmosphere at a level that would not allow dangerous anthropogenic impact on the climatic system of the planet. The foreign experience of financing environmental protection is described and the possibilities of their introduction in the national practice are determined.